Enzymic treatment of leather intermediate product in the process of softening - Данилкович, Анатолій Григорович; Романюк, Оксана Олександрівна (Eastern-European Journal of Enterprise Technologies, 2014)
Using enzyme preparations in animal hide treatment technologies is caused by their strong and specific catalytic action in various chemical transformations. The influence of the concentration of proteolytic enzymes - pancreatin and Chemizym BH and treatment duration on the process of softening the hide of wet-salted bull by canning method after unhairing - ashing, washing, splitting and deashing was studied. The effectiveness of the enzymes was estimated by determining the amount of the melted gelatin from deashed and softened hide and physicochemical properties of intermediate products. At the enzyme preparation concentration of 2.2 g/L, temperature of 35-37°C and long-term hide softening, amount of melted gelatin from the dermis reaches 45.0%, and for papillary layer this indicator is close to 100%. The results obtained were used in manufacturing the intermediate product “Crust”. The studies of physical-mechanical properties of the intermediate product “Crust” have allowed to determine softening duration that provides an optimal range of performance properties. The results obtained can be used for softening process optimization in the manufacturing technology of the intermediate product “Crust” in order to ensure the required material quality at the expenditure rate of enzyme Chemizym BH of 0.3% and water of 100% of the ashed hide mass. Twelve-hour unhairing - rawhide ashing and one-hour hide softening at the optimum action of enzyme Chemizym BH can be considered effective in the manufacturing technology of boxcalf materials for footwear, clothes and fancy goods.